ANALISIS PENGEMBANGAN SUMBER DAYA MANUSIA PADA DINAS PENDIDIKAN KLATEN - Widyastuti, Erma; Riantisari, Rahmawati (Jurnal Manajemen, 2023)
Human resources are the most important part of the organization, because of their role as a driving force for the organization to achieve prosperity by using the skills and knowledge they have. This study aims to analyze how human resources develop in the Klaten Education Office. This research is qualitative with the analytical method used, namely qualitative descriptive analysis. The research sample is Plt. Head of General Affairs and Personnel Subdivision of the Klaten Education Office. The results of the study illustrate that the development of human resources at the Klaten Education Office uses the training method. The implications of the research results can be used as material for consideration by the Klaten Education Office as material in carrying out the human resource development process so that the program provided with the desired results can be appropriate. Develop Human Resources, Klaten Education Office